2015
DOI: 10.1128/aem.03214-14
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and Phenotypic Characterization of Escherichia coli Isolates from Feces, Hands, and Soils in Rural Bangladesh via the Colilert Quanti-Tray System

Abstract: The increased awareness of the role of environmental matrices in enteric disease transmission has resulted in the need for rapid, field-based methods for fecal indicator bacteria and pathogen detection. Evidence of the specificity of β-glucuronidase-based assays for detection of Escherichia coli from environmental matrices relevant to enteric pathogen transmission in developing countries, such as hands, soils, and surfaces, is limited. In this study, we quantify the false-positive rate of a β-glucuronidase-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 51 publications
2
34
0
Order By: Relevance
“…Thus, several studies have validated the Colilert system on different matrices, such as raw meat, fresh-cut products, and marine and other types of water samples [8][9][10][11][12][13]. Our findings supported the results of Julian et al [28] that 98.9% of presumptive E. coli isolated from hands, soil, and fecal samples using the Colilert reagent was finally confirmed as E. coli. Kawasaki et al [11] reported that E. coli was detectable from vegetables using the DOX system with Colilert-18.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Thus, several studies have validated the Colilert system on different matrices, such as raw meat, fresh-cut products, and marine and other types of water samples [8][9][10][11][12][13]. Our findings supported the results of Julian et al [28] that 98.9% of presumptive E. coli isolated from hands, soil, and fecal samples using the Colilert reagent was finally confirmed as E. coli. Kawasaki et al [11] reported that E. coli was detectable from vegetables using the DOX system with Colilert-18.…”
Section: Discussionsupporting
confidence: 88%
“…The accuracy of the Colilert system can be impacted by both the aforementioned microbiota within the matrix and the matrix itself. For example, the acidity in fruit juice impairs the fluorescence of 4-methylumbelliferone [28]. Thus, several studies have validated the Colilert system on different matrices, such as raw meat, fresh-cut products, and marine and other types of water samples [8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally the results on (Tab.1) revealed the prevalence of E.coli isolation from milk samples from different infected animals based on culturing identification. where 88% isolates were identified as E. coli (27). A recently report revealed E.coli isolated from mastitic milk samples were identification by the API 20 E showed about 12.4% as E.coli (28).…”
Section: Resultsmentioning
confidence: 92%
“…The placement of soil E. coli in terminal lineages of the phylogeny with fecal E. coli suggests the fluidity and lack of phylogenetic structure based on source. Humans and animals are suggested as likely contributors to the E. coli population in soils (28,35), but clonality or an estimate of the time of diversification between E. coli in soil and E. coli from the input source has not yet been established. Mutation rates are routinely used to establish time of diversification (36,37).…”
Section: Discussionmentioning
confidence: 99%